Finite element analysis and structural optimization of V-shaped seal ring based on ANSYS Workbench. Issue 1 (1st December 2022) - Guo, Zhounan; Li, Hui; Gu, Chang
Abstract : Based on the finite element analysis software of ANSYS Workbench, the sealing performance of a V-shaped seal ring is analyzed. It is found that the position of the maximum shear stress of the V-shaped seal ring is on both sides of the bottom of the opening. Then, the effects of root height h and opening arc diameter D on the maximum shear stress and maximum contact pressure of the seal ring are studied, and the parameters are optimized accordingly. Further, the ultimate working pressure of the optimized structure is analyzed. The results show that the maximum shear stress and maximum contact pressure of the seal ring increase with the root height, but there is a downward inflection point at h-0.2. The maximum shear stress of the seal ring increases with the opening arc diameter, but there is a rising inflection point at D-0.2. Further, the maximum contact pressure of the seal ring first increases rapidly and then increases slowly with the opening diameter. The working oil pressure that the V-shaped seal ring can bear is 1.3 MPa. The simulation results can guide the design of the V-shaped seal ring.